The Archive as Dumpster - Hogan, Mél (Pivot: A Journal of Interdisciplinary Studies and Thought, 2015)
In four exploratory theoretical gestures (appraise, dispose, hoard and mediate), I propose the ‘archive as dumpster’ as a framework for returning to the physical conditions of memory, where “picking through the trash” subverts traditional archival methodologies by insisting on the very material consequences of a culture inculcated in networked digital communications. I make an argument that by posing the archive as a mediatic question (Parikka 2013), we can begin to account for the ways in which the perceived immateriality and weightlessness of our data is in fact with immense humanistic, environmental, political, and ethical repercussions. It is also a means by which we come to understand who we are, looking forward. In both cases, pitting the archive’s orderly ambitions against the dumpster’s stinking mess reveals a ‘call of things’ (Bennett 2011); the slow and often distanced process of disposal and waste to remind us who we are, in and over time, in and out of our bodies, increasingly under the impression of a dematerialised engagement with our stuff.